Effects of advanced glycation end products on stem cell - Zheng, Zetai; Zhou, Hui; Zhang, Wenwen; Wang, Tingyu; Swamiappan, Sathiskumar; Peng, Xinsheng; Zhou, Yanfang (Frontiers in Cell and Developmental Biology, 2024)
In recent years, stem cell therapy has become a pivotal component of regenerative medicine. Stem cells, characterized by their self-renewal capacity and multidirectional differentiation potential, can be isolated from a variety of biological tissues, including adipose tissue, bone marrow, the umbilical cord, and the placenta. The classic applications of stem cells include human pluripotent stem cells (hPSCs) and mesenchymal stem cells (MSCs). However, numerous factors can influence the normal physiological function of stem cells. For instance, in diabetes mellitus, advanced glycation end products (AGEs) accumulate in the extracellular matrix (ECM), impairing the physiological function of stem cells. These substances are closely associated with aging and the progression of numerous degenerative diseases. AGEs can create an environment that is detrimental to the normal physiological functions of stem cells. By binding to the primary cellular receptor for advanced glycation end products (RAGE), AGEs disrupt the physiological activities of stem cells. The binding of RAGE to various ligands triggers the activation of downstream signaling pathways, contributing to the pathophysiological development of diabetes, aging, neurodegenerative diseases, and cancer. Therefore, there is an urgent need for comprehensive research on the impact of AGEs on stem cells, which could provide new insights into the therapeutic application of stem cells in regenerative medicine.